Limnellia helmuti - Nunes, Rui (2021)
JUSTIFICATION: Limnellia helmuti is an endemic species of the Azores (Portugal), being present (at least historically) on S. Miguel island. From the historical data, this species has only been recorded in a disturbed area (Furnas) and would have a very small Extent of Occurrence (8 km²) and Area of Occupancy (8 km²). It is possible that this species has declined in the past as a result of human activity. However, the present situation of this species needs to be further assessed and further research is needed into its population, distribution, threats, ecology and life history; while conservation of native wet and boggy areas and other water bodies could potentially aid this species conservation. Based upon the lack of recent in data regarding this species population, distribution, threats and ecology, this species is assessed as Data Deficient (DD).